Farmers’ willingness to adopt geographical indication practice in Indonesia: A psycho behavioral analysis - Pandu Laksono; Irham; Jangkung Handoyo Mulyo; Any Suryantini (Heliyon, 2022)
The paper examined the factors influencing farmer’s willingness to adopt GI (geographical indication) practices in the Indonesian coffee sector from a psycho behavioral perspective. Specifically, the paper examined the psychological factors influencing the willingness of farmers to adopt GI. The study combined (1) the Planned Behavior (TPB) theory and (2) Technology Acceptance Model (TAM) as the theoretical framework. The following psycho behavioral factors were constructed and tested: subjective norm (SN), perceived behavioral control (PBC), attitudes toward behavior (ATB), perceived usefulness (PU) and perceived economic benefit (PEB). The study also investigated the effects of sociodemographic factors on these psycho behavioral constructs. The survey was conducted in two geographical indication coffee territories in Indonesia that involved 178 farmers who are perceived as willing to adopt GI practices and procedures. The relationship between constructs was investigated in which structural equation modeling (SEM) was used. The obtain data were analyzed using WarpPLS 7.0. The study finds that attitude toward behavior, perceived behavioral control, and perceived economic benefit, as important factors influencing the willingness to adopt GI practices. The subjective norm did not affect willingness to adopt GI practices. Farmers’ knowledge mainly affected perceived behavioral control and willingness to adopt GI practices and procedures.